Decolonization of care through a wholistic way of living: Gaga from the Tayal in Taiwan - Wasiq Silan; Chi-Chuan Chen; Tin-Yu Lai (Canadian Science Publishing, 2022)
This article explores the "wholistic" as a central concept of "the good life" as expressed by the Bnkis, Tayal Indigenous Elders, who participated in the Day Club, Tayal territory of Northern Taiwan. In particular, we analyze the stories of care experienced by the Bnkis from the standpoint of wholistic relationships. The stories were recorded primarily between 2015 and 2018. In this analysis we used a critical qualitative design approach, privileging Tayal epistemology and informed by Tayal hermeneutics. Our results show that the concept of well-being for the Bnkis is closely linked to their relationships with people and with the land and spirituality. Through these relationships, the continuation of Gaga-Tayal law and cosmology-has been adapted organically over time. We argue that Gaga is central to Tayal Elder/Bnkis care and essential to Bnkis' well-being. We propose that the concept of wholistic relationships embedded in the Tayal law of Gaga is vital in developing an elderly care system that is genuinely culturally relevant in the long run. This research demonstrates how the wholistic concept can improve human health and well-being, and ultimately provides an implication to sustainable development.